Application Of The M-Apos Learning Model (Modification-Action, Process, Object, Scheme) To Improve Mathematics Outcomes In Class IV State Elementary School 011 Rambah Samo - Rezi Intan; Rejeki Rejeki; Rika Rosanti Panggabean; Indah Permata Sari; Sri Yunita Sari (Indonesian Journal of Basic Education, 2022)
This study aims to find out that the application of M-APOS learning to improve mathematics learning outcomes for fourth grade students at SD Negeri 011 Rambah Samo. The background that underlies this research is the failure to achieve the learning objectives as illustrated by the students' daily test scores in mathematics learning which are still below the KKM score of 75. The subjects in this class action research were 29 students of SD Negeri 011 Rambah Samo, consisting of 14 female students and 15 male students. The data analysis technique used in this study was to use several instruments in the form of question sheets and student activity observation sheets. The results of this study can be seen from the first cycle of students who completed 50% (17 students) and 43% (11 students) did not complete with an average score of 65.30, increased by 60% (19 students) ). , then experienced an increase in meeting 2, with 92% (22 students) completing and 8% (7 students) not completing with an average score of 90.5. With an increase in learning outcomes there is an increase in the activity of teachers and students. Based on these learning outcomes it can be said that there was an increase in student learning outcomes from cycle 1 to cycle 2 by 35%. When viewed from the data that has been obtained, it can be seen that those who passed have exceeded the indicators of success. So it can be concluded that the application of M-APOS learning to improve Mathematics learning outcomes for fourth grade students at SD Negeri 011 Rambah Samo has been successful.